Effect of Rate and Method of Nitrogen and Phosphorus Application on seed Production in Iseilema Laxum Hack - Shankarnarayan, K A; Rai, P (Annals of Arid Zone, 2016)
Studies on methods of application of nitrogen and phosphorus during 1967 and 1968 revealed that there was significant response of nitrogen on the seed yield of Iseilema laxum in both the years. Soil application of nitrogen was found to be beneficial over top dressing and foliar spray. Significant effect of phosphorus was observed during 1968 only. Interaction of nitrogen and phosphorus was not found to be significant. However, the maximum seed yield in 1967 (248.69 kg/ha) and 1968 (103.90 kg/ha) was obtained with the treatment combination of 60 kg N/ha as soil applicarion and 20 kg P2O5/ha as foliar spray and 60 kg N/ha x 20 kg P2O5/ha as soil application, respectively.